Glycerol Acetylation with Propionic Acid Using Iron and Cobalt Oxides in Al-MCM-41 Catalysts - Fabio Ribeiro Tentor; Diego Borelli Dias; Mateus Rosolen Gomes; João Guilherme Pereira Vicente; Lúcio Cardozo-Filho; Marcio Eduardo Berezuk (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
In this work, Al-MCM-41 molecular sieves were synthesized, containing iron and/or cobalt oxides, impregnated by incipient wetness method, characterized and applied as catalysts in the acetylation reaction of glycerol with propionic acid to produce green glyceryl propionate molecules of high commercial value. According to this, X-ray Diffraction (XRD), X-ray Fluorescence (XRF), Fourier Transform Infra Red (FT-IR), adsorption/desorption N2 isotherms, textural analysis, and Scanning Electron Microscope (SEM) analysis were recorded to evaluate the main characteristics of materials. The presence of Lewis and Brønsted acidic sites and catalysts surface area were observed as important key points to functionalize acetylation reaction. Thus, time reaction, temperature, and glycerol / propionic acid ratio varied to improve the most suitable reaction conditions and behaviors. As a result, glycerol conversion was above 96%, followed by 68% of selectivity to glyceryl monopropionate as well as the formation of glyceryl di- and tri- propionate and a small amount of ethylene glycol dipropionate as an undesired product. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).